Antifolate SERS-active nanovectors: quantitative drug nanostructuring and selective cell targeting for effective theranostics. Issue 32 (6th August 2019) - Fasolato, Claudia; Giantulli, Sabrina; Capocefalo, Angela; Toumia, Yosra; Notariello, Daniele; Mazzarda, Flavia; Silvestri, Ida; Postorino, Paolo; Domenici, Fabio
Abstract : Antifolate plasmonic nanovectors (NVs) are proposed. SERS and cytotoxicity studies on non-cancer and cancer cells reveal the efficient targeting and killing of cancer cells. The selectivity is optimized by coloading folate and antifolate on the NV. Abstract : One of the frontiers of nanomedicine is the rational design of theranostic nanovectors. These are nanosized materials combining diagnostic and therapeutic capabilities, i.e. capable of tracking cancer cells and tissues in complex environments, and of selectively acting against them. We herein report on the preparation and application of antifolate plasmonic nanovectors, made of functionalized gold nanoparticles conjugated with the folic acid competitors aminopterin and methotrexate. Due to the overexpression of folate binding proteins on many types of cancer cells, these nanosystems can be exploited for selective cancer cell targeting. The strong surface enhanced Raman scattering (SERS) signature of these nanovectors acts as a diagnostic tool, not only for tracing their presence in biological samples, but also, through a careful spectral analysis, to precisely quantify the amount of drug loaded on a single nanoparticle, and therefore delivered to the cells. Meanwhile, the therapeutic action is implemented based on the strong toxicity of antifolate drugs. Remarkably, supplying the drug in the nanostructured form, rather than as a free molecule, enhances its specific toxicity. The selectivity of the antifolate nanovectors can be optimized by the design of a hybrid folate/antifolate coloaded nanovector for the specific targeting of folate receptor α, which is overexpressed on numerous cancer cell types.